Non-metric traits, physiological stress indicators and paleopathological lesion on human skeletal remains from an early modern cemetery in Wyszyński Street, Wrocław, Poland (15th–18th centuries AD) - Tomaszewska, Agnieszka; Kwiatkowska, Barbara (Anthropological Review, 2019)
The anthropological analysis and assessment of the living conditions of historical populations should be comprehensive. Due to the scarcity of the well-preserved skeletal remains of a population buried at the cemetery in Wyszyński Street, Wrocław, each piece of information is particularly important in providing the complementary information about living and health conditions of late medieval and early modern inhabitants of Wrocław. This study aims to assess the living conditions of the late medieval and early modern Wrocław inhabitants. This aim was reached by analyzing the frequency of non-metrical cranial and postcranial traits, physiological stress indicators, and pathological lesions. The importance of these traits for population studies is also discussed. For 98 skeletons (22.4% male and 37.8% female) from a cemetery located in Wyszyński Street, (15th –18th centuries AD), the frequencies (p) of the following traits were analyzed: 38 non-metric cranial and 9 post-cranial traits, the morphological indicators of physiological stress (i.e. cribra orbitalia and enamel hypoplasia), caries and pathological lesions on bones. Among the non-metric cranial traits, only nine (23.7%) were not observed. The most frequent (from p= 0.30 to p=0.65) were foramen parietale, incisura frontalis accesoria seu foramen frontale accesorius, foramen supraorbitale, M3 mandibulare, ossicula suturae lambdoideae, and foramen mastoideum extrasuturale. Only three non-metric post-cranial traits were observed, but with low frequency (p=0.01 and 0.02). Cribra orbitalia was present in 37.0% of the skeletons while enamel hypoplasia was present in only 2.6%. Susceptibility to caries occurred in 68% of the cases while carries lesions occurred in 31.2%. Among pathological changes, the most frequent were degenerative changes (21.6%) and injuries (19.6%). Owing to the poorly preserved remains, the complete assessment of the living conditions of the population was difficult. The number of the observed traits would have probably increased, had the number of complete and well-preserved skeletons been higher. The results of the study suggest that the living conditions of the studied population were poor. It is hypothesized that the cemetery was a burial place for prisoners and victims of various epidemics that affected the city. But since the historical sources of this cemetery are scarce, it is hard to unequivocally state its purpose with certainty.